2011
DOI: 10.1175/2010mwr3456.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Ensemble Predictions of 2009’s Tropical Cyclones Initialized with an Ensemble Kalman Filter

Abstract: Verification was performed on ensemble forecasts of 2009 Northern Hemisphere summer tropical cyclones (TCs) from two experimental global numerical weather prediction ensemble prediction systems (EPSs). The first model was a high-resolution version (T382L64) of the National Centers for Environmental Prediction (NCEP) Global Forecast System (GFS). The second model was a 30-km version of the experimental NOAA/ Earth System Research Laboratory's Flow-following finite-volume Icosahedral Model (FIM). Both models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
120
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 86 publications
8
120
0
1
Order By: Relevance
“…The central pressure of the TCs is systematically weaker in both analyses and forecasts than in the best-track data. This is consistent with the results of Hamill et al (2010), who concluded that global models with their relatively coarse resolution are still not able to provide realistic TC intensity forecasts.…”
Section: Impact On Ensemble Forecastssupporting
confidence: 91%
See 4 more Smart Citations
“…The central pressure of the TCs is systematically weaker in both analyses and forecasts than in the best-track data. This is consistent with the results of Hamill et al (2010), who concluded that global models with their relatively coarse resolution are still not able to provide realistic TC intensity forecasts.…”
Section: Impact On Ensemble Forecastssupporting
confidence: 91%
“…We follow the approach of Hamill et al (2010) to calculate the mean spread of the experiments. We only use a forecast if it is possible to identify the TC at least in 40% of the ensemble members at the respective forecast time.…”
Section: Impact On Ensemble Forecastsmentioning
confidence: 99%
See 3 more Smart Citations